Sexualised video games, sexist attitudes and empathy towards victims of rape: Correlational evidence for a relationship is minimal in an online study. (23rd January 2020) - Ferguson, Christopher J.; Colwell, John
Abstract: Background: There is continued debate about whether sexualisation in games can influence sexist attitudes and reduced empathy towards women in real life. There is research evidence both supporting and refuting the possibility. Aims: Our aim was to examine the relationship between sexualised content in video games and players' sexist attitudes and empathy. Our research question was, do any such relationships exist once other factors including gender and trait aggression are controlled? Methods: An online sample of 125 participants were recruited and asked to rate their video game playing experience, complete a trait aggression scale and record responses to a vignette about rape. Scores were first correlated, and then hierarchical multiple regression was employed followed by PROCESS examination of interactions between sexualised game content and trait aggression. Results: Exposure to sexualised content in video games was neither correlated with higher sexist attitude ratings nor with lower empathy scores. Sexualised content in games was associated with slightly lower sexist belief scores for those with higher scores on trait aggression (the 12.8% of our current sample at one standard deviation above the mean). No effects were observed for those low in trait aggression. Conclusions and Implications: While it is natural to be concerned about the impact of potentially arousing video games, actual effects may be counterintuitive, so if seeking to regulate, it is important to act from actual information. Further research with groups of particular concern will be important.